Pendapatan, Konsumsi dan Tingkat Kesejahteraan Pengrajin Batik Wanita KUB Pringmas di Desa Papringan Banyumas - Recha Pangestika; Herman Sambodo; Goro Binardjo; Sodik Dwi Purnomo (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2021)
The purpose of this study was to analyze the contribution of women's batik craftsmen income to household income, the influence of KUB Pringmas women's batik craftsman income on consumption expenditure and the welfare level of KUB Pringmas women's batik craftsmen. The population were 38 respondents. Data collection techniques through observation accompanied by interviews and questionnaires. The results of research using analytical techniques in the form of cross tabulation and simple linear regression showed that: (1) As many as 94.74% or 36 women batik craftmen contributed low, the average income of female batik artisans was less than Rp 1,116,667 per month. The income of female batik craftmen has a significant positive effect on household consumption. (3) The batik craftsmen of KUB Pringmas are included in the category of not yet prosperous, but household welfare using the BKKBN indicator has been met and the average is in the condition Prosperous Family III Plus (KS III Plus). The implication of the above conclusion is that the efforts of women artisans to increase their income contribution to the household by making the main work and increasing working hours. Food consumption expenditure takes precedence over non-food consumption. Efforts to improve welfare by holding training to improve the skills of women batik craftmen.